Etiology of Above-knee Amputations in the United States: Is Periprosthetic Joint Infection an Emerging Cause?. Issue 10 (October 2018) - George, Jaiben; Navale, Suparna M.; Nageeb, Emmanuel M.; Curtis, Gannon L.; Klika, Alison K.; Barsoum, Wael K.; Mont, Michael A.; Higuera, Carlos A.
Abstract: Background: Above-knee amputation (AKA) is a morbid procedure and is performed for a number of conditions. Although AKA is usually performed for dysvascular disease, trauma, and malignancy, AKA is also considered in patients who have failed multiple salvage attempts at treating periprosthetic joint infection (PJI) of TKA. Although aggressive measures are being taken to treat PJI, the huge volume of TKAs might result in a large number of AKAs being performed for PJI in the United States. However, the national trends in the incidence of AKAs from different etiologies and the relative contribution of different etiologies to AKA are yet to be studied. Questions/purposes: (1) What are the temporal trends in the incidence of AKAs (from all causes) in the US population from 1998 to 2013? (2) What are the temporal trends in the incidence of AKAs by etiology (dysvascular disease, trauma, malignancy, and PJI)? (3) What are the temporal trends in the relative contribution of different etiologies to AKA? Methods: Using the Nationwide Inpatient Sample (NIS) from 1998 to 2013, AKAs were identified using International Classification of Diseases, 9 th Revision (ICD-9) procedure code 84.17. The NIS database is the largest all-payer database in the United States containing information on approximately 20% of all the hospital admissions in the country. As a result of its sampling design, it allows for estimation of procedural volumes at the national level. All AKAs were grouped into one of the following five etiologies in a sequential manner using ICD-9 diagnosis codes: malignancy, PJI, trauma, dysvascular disease (peripheral vascular disease, diabetic, or a combination), and others. All of the numbers were converted to national estimates using sampling weights provided by the NIS, and the national incidence of AKAs resulting from various etiologies was calculated using the US population as the denominator. Poisson and linear regression analyses were used to analyze the annual trends. Results: From 1998 to 2013, the incidence of AKAs decreased by 47% from 174 to 92 AKAs per 1 million adults (incidence rate ratio [IRR]; change in the number of AKAs per 1 million adults per year; 0.96; 95% confidence interval [CI], 0.96-0.96; p < 0.001). The incidence of AKAs resulting from PJI increased by 263% (IRR, 1.07; 95% CI, 1.06-1.07; p < 0.001). An increase was also observed for AKAs from malignancy (IRR, 1.01; 95% CI, 1.00-1.02; p = 0.007), although to a smaller extent. AKAs from dysvascular causes (IRR, 0.96; 95% CI, 0.95-0.96; p < 0.001) and other etiologies (IRR, 0.97; 95% CI, 0.96-0.97; p < 0.001) decreased. There was no change in the incidence of AKAs related to trauma (IRR, 1.00; 95% CI, 0.99-1.00; p = 0.088). The proportion of AKAs resulting from PJI increased by 589% from 1998 to 2013 (coefficient = 0.18; 95% CI, 0.15-0.22; p < 0.001). The proportion of AKAs resulting from dysvascular causes decreased (coefficient = 0.18; 95% CI, 0.15-0.22; p < 0.001), whereas that resulting from malignancy (coefficient = 0.04; 95% CI, 0.03-0.05; p < 0.001) and trauma (coefficient = 0.13; 95% CI, 0.09-0.18; p < 0.001) increased. Conclusions: The incidence of AKAs has decreased in the United States. AKAs related to dysvascular disease and other etiologies such as trauma and malignancy have either substantially decreased or remained fairly constant, whereas that resulting from PJI more than tripled. Given the increased resource utilization associated with limb loss, the results of this study suggest that national efforts to reduce disability should prioritize PJI. Further studies are required to evaluate the risk factors for AKA from PJI and to formulate better strategies to manage PJI. Level of Evidence: Level III, therapeutic study.